Hydrodynamic influences on acoustical and optical backscatter in a fringing reef environment. Issue 1 (20th January 2017) - Pawlak, Geno; Moline, Mark A.; Terrill, Eric J.; Colin, Patrick L.
Abstract: Observations of hydrodynamics along with optical and acoustical water characteristics in a tropical fringing reef environment reveal a distinct signature associated with flow characteristics and tidal conditions. Flow conditions are dominated by tidal forcing with an offshore component from the reef flat during ebb. Measurements span variable wave conditions enabling identification of wave effects on optical and acoustical water properties. High‐frequency acoustic backscatter (6 MHz) is strongly correlated with tidal forcing increasing with offshore directed flow and modulated by wave height, indicating dominant hydrodynamic influence. Backscatter at 300 and 1200 kHz is predominantly diurnal suggesting a biological component. Optical backscatter is closely correlated with high‐frequency acoustic backscatter across the range of study conditions. Acoustic backscatter frequency dependence is used along with changes in optical properties to interpret particle‐size variations. Changes across wave heights suggest shifts in particle‐size distributions with increases in relative concentrations of smaller particles for larger wave conditions. Establishing a connection between the physical processes of a fringing tropical reef and the resulting acoustical and optical signals allows for interpretation and forecasting of the remote sensing response of these phenomena over larger scales. Key Points: Optical and high‐frequency acoustic backscatter is strongly linked to wave and tidal forcing for a tropical forereef Changes in properties indicate relative increases in smaller particles with increasing wave forcing Variations in modeled reflectance spectra indicate particles are consistent with whiting events